Migration motivations of internally displaced people: The view from Homs: Preliminary findings of an impact assessment and repatriation programme - Gibarti, Sara; Solymári, Dániel (Journal of Regional Security, 2023)
The Syrian conflict led to a countrywide realignment in both territorial and demographic traits with catastrophic consequences for the population. More than 6.6 million people were forced to leave their homeland, and a further 6.7 million became Internally Displaced Persons (IDPs). Lately a subsequent consolidation of the population ensued which witnessed a partial self-repatriation of IDPs. Here, we report the preliminary results of a study to explore migration motives in the framework of the repatriation aid programme provided for these IDPs. The programme is jointly coordinated by the Melkite Greek Catholic Archeparchy of Homs and the Hungary Helps Program, in and around the city of Homs. Moreover, we provide an overview of the geographic territory covered by the programme, and of the relevant events of the conflict which affected IDPs from the region. Key results from our analysis include the observation that individual experiences of traumatisation and deterioration of social status are major contributing factors that fuel resettlement. Our work casts valuable light on the triggers of internal migration and timely guidance to ongoing struggles and newly emerging conflicts such as that of Ukraine in 2022.